Lymph Nodes Dissection in Elderly Patients with T3-T4 Laryngeal Cancer - Pan Y (Dove Medical Press, 2020)
Yafeng Pan,1 Xuye Zhao,2 Dean Zhao,1 Junhua Liu1 1Department of Otolaryngology, Xiang’an Hospital of Xiamen University, Xiamen, Fujian, People’s Republic of China; 2Department of Breast and Thyroid Surgery, Xiang’an Hospital of Xiamen University, Xiamen, Fujian, People’s Republic of ChinaCorrespondence: Junhua LiuDepartment of Otolaryngology, Xiang’an Hospital of Xiamen University, Xiamen, Fujian 361101, People’s Republic of ChinaEmail xaherbihou@163.comObjective: To explore the survival value of lymph node dissection (LND) in elderly patients with T3-T4 laryngeal cancer, analyze the risk factors of lymph node metastasis, and construct a preoperative prediction model.Materials and Methods: The study included 996 patients aged ≥ 65 years with laryngectomy confirmed T3-T4 laryngeal cancer queried from Surveillance, Epidemiology and End Results (SEER) database between 2010 and 2017. Propensity score matching (PSM) was applied to balance the effects of confounding factors. Kaplan–Meier (K–M) analysis and competitive risk model were used to compare the overall survival (OS) and cancer-specific survival (CSS) between LND and no-LND (N-LND) group. Combined with risk factors of multivariate logistic regression, a nomogram was built to predict lymph node metastasis preoperatively. The performance was assessed in the training set and the validation set, and internal validation was assessed.Results: Among the cohort, 822 patients underwent LND and 410 patients had positive lymph nodes. The OS and CSS of patients who underwent LND were not better than that of N-LND patients (P> 0.05). The prognosis of patients with lymph node metastases was significantly worse than that of negative patients (P< 0.05). On multivariate logistic regression, supraglottis cancer, tumor size > 5cm and grade 3– 4 classification were associated with significantly greater odds of lymph node metastasis. The nomogram showed favorable predictive efficacy and good calibration (in the training cohort C-index=0.700; in the validation cohort C-index=0.721).Conclusion: For elderly patients with T3-T4 laryngeal cancer, LND did not bring significant survival values. Supraglottis cancer, tumor size > 5cm and grade 3– 4 classification were independent risk factors of lymph node metastasis, which means poor prognosis. The nomogram developed was an easy-to-use tool for lymph node prediction.Keywords: elderly, T3-T4 laryngeal cancer, lymph node dissection, survival, nomogram